Characterization of a blaKPC-3-carrying plasmid in a clinical isolate of Klebsiella pneumoniae belonging to the emerging successful clone ST147 - Esther Recacha; Mercedes Delgado-Valverde; Marina R. Pulido; Elena Pérez-Nadales; Patricia Pérez-Palacios; Inés Portillo-Calderón; Juan Manuel Sánchez-Calvo; Irene Gracia-Ahufinger; Álvaro Pascual (Microbiology Spectrum)
ABSTRACT Klebsiella pneumoniae ST147 has emerged as a successful clone able to efficiently disseminate a number of carbapenemases, including blaKPC. This study compared a representative blaKPC-3-carrying plasmid of an ST147 clone with plasmids that usually harbor blaKPC-3 belonging to the high-risk clone ST512. Five clinical isolates of KPC-3-producing K. pneumoniae belonging to ST147 isolated in Southern Spain were analyzed. The first ST147 isolate detected was compared with two previous isolates of K. pneumoniae ST512/KPC-3 and KPC-3-encoding plasmid pKpQIL as reference plasmid. Microdilution, disk diffusion, β-CARBA test, and NG-Test CARBA 5 were used for antimicrobial susceptibility analysis and phenotypic characterization of the isolates according to EUCAST guidelines. Molecular characterization was performed using pulsed-field gel electrophoresis (PFGE)-XbaI, sequenced (by Illumina and Oxford Nanopore) and annotated with open-source databases (CGE tools and RAST). Plasmid incompatibility groups were analyzed using PlasmidFinder; BRIG was used to compare the blaKPC-3-harboring plasmids from three of the selected clinical isolates with each other and with pKpQIL. Clinical isolates of ST147/KPC-3 showed resistance to β-lactams, fluoroquinolones, and aminoglycosides. Clinical isolates ST147/KPC-3 and ST512/KPC-3 had identical PFGE patterns in each clone. Plasmid replicon analysis showed a plasmid with the formula IncFII (K2:A-:B-) in the ST512 isolates, identical to pKpQIL; the ST147 isolates harbored IncFII (K1:A-:B-), although the genetic environment of blaKPC-3 was the same as pKpQIL, which is Tn4401_ISKpn7 upstream of blaKPC-3 and ISKpn6 downstream of blaKPC-3. Plasmids harboring blaKPC-3 in ST147 and ST512 are different, although differences are subtle. The genetic environment of blaKPC-3 in the different sequence types is very conservative and identical to pKpQIL.IMPORTANCEThe successful spread of blaKPC is primarily due to the dissemination of K. pneumoniae isolates belonging to high-risk clonal complex 258 (ST258, ST11, and ST512); however, new clones are emerging globally as the ST147 clone. In this study, we compare the genetic environment of a representative blaKPC-3-carrying plasmid of an ST147 clone with plasmids that usually harbor blaKPC-3 belonging to the high-risk clone ST512. Plasmids harboring blaKPC-3 detected in ST512 and ST147 were different; however, the close genetic environments of blaKPC-3 in the different plasmids (ST147 and ST512) remained conserved.